Silica powder with reduced aggregation, resin composition, and semiconductor encapsulant

A silica powder with D50 of 2.0 μm or less and Dmax of 5.0 μm or less, produced via air classification, addresses agglomeration issues, enhancing dispersibility and handling in resin compositions for semiconductor encapsulants.

JP7599556B2Active Publication Date: 2024-12-13DENKA CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023520999
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-05-13
Filing Date
2022-05-06
Publication Date
2024-12-13
Estimated Expiration
2042-05-06

AI Technical Summary

Technical Problem

Silica powders with an average particle diameter of 2.0 μm or less tend to aggregate, causing handling difficulties, clogging in transportation, and reducing dispersibility in resin compositions, leading to semiconductor damage and molding defects.

Method used

A silica powder with a volume-based cumulative diameter (D50) of 2.0 μm or less and a maximum particle diameter (Dmax) of 5.0 μm or less, achieved through air classification using the Coanda effect, ensuring good dispersibility and handling properties.

Benefits of technology

The silica powder effectively prevents agglomeration and ensures easy dispersion in resin compositions, reducing the risk of semiconductor damage and improving handling efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007599556000001
    Figure 0007599556000001
Patent Text Reader

Abstract

Provided are: a silica powder having a particle size of 2.0 μm or less, said silica powder not easily aggregating, having good handling, and easily dispersing when mixed with a resin; and a resin composition and a semiconductor sealing material including the silica powder. The silica powder has a volume-based cumulative size (D50) of 2.0 μm or less, and a maximum particle size (Dmax) of 5.0 μm or less measured via a grind gauge using the stated method. Measurement method: For a resin composition obtained by adding 67 parts by mass of the silica powder to 100 parts by mass of a bisphenol F-type liquid epoxy resin, in accordance with JIS K 5600-2-5, using a grind gauge, evaluate the dispersion degree of the silica powder into the epoxy resin via a distribution map method, and measure maximum particle size (Dmax). Moreover, carry out the same evaluation 5 times, and use the average value thereof.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a silica powder with reduced aggregation, a resin composition, and a semiconductor encapsulant. [Background technology]

[0002] In silica powders used for semiconductor encapsulation and insulating substrate applications, agglomerated particles and coarse particles are required to be reduced because they cause package damage, lead wire shorts, unevenness on the substrate, white spots, etc. In addition, when silica powders containing coarse particles are blended with a resin, they cause a decrease in the flowability of the resin, and when such a resin composition is used as a semiconductor encapsulation material, semiconductor damage, molding defects, etc. are likely to occur. From these viewpoints, a silica powder that is less likely to aggregate and has fewer coarse particles is required.

[0003] Incidentally, it is known that silica powders having an average particle size of 2.0 μm or less tend to aggregate due to the forces acting on the silica powder (weight, liquid bridging force, van der Waals force, etc.). Silica powders having such particle sizes also have a high adhesion to equipment and containers, which causes the silica powder to clog transport pipes and feeders, making handling difficult. In light of this background, silica powders having a particle size of 2.0 μm or less have a very low yield when classified using a sieve, making it difficult to produce silica powders with few coarse particles. In addition, the silica powders aggregate and become coarse even when vibrated by a sieving device, which makes it difficult to obtain the desired dispersibility when mixed with a resin.

[0004] In recent years, in response to the demand for smaller, lighter, and more powerful electronic devices, the internal structure of semiconductors has been rapidly developing, with thinner elements, smaller gold wires, longer spans, and higher density wiring pitches. As a sealing material for such semiconductors, a resin composition containing a silica powder with a smaller average particle size as a filler is required, but as mentioned above, silica powder with a smaller average particle size is prone to aggregation and is difficult to handle. Therefore, a silica powder with a small particle size that is less prone to aggregation, has a small content of coarse particles, and is easy to handle is required.

[0005] Regarding this problem, for example, Patent Document 1 discloses a method for reducing the BET to 2m 2 / g or more 30m 2 / g and a silica powder with a particle content of 1.5 μm or more of less than 0.1 mass%. However, in Patent Document 1, coarse particles are removed by wet classification, so that the particle size distribution and specific surface area change due to the reduction of fume components on the powder surface, and dispersibility in resin decreases. In addition, Patent Document 2 proposes a spherical silica fine powder having a particle size distribution maximum in the range of 1 μm to 10 μm, and a coarse particle residue on a sieve with a mesh size of 45 μm or less of 0.01 weight%. However, in the method of Patent Document 2, it is difficult to remove only the coarse particles without changing the particle size distribution. In addition, Patent Documents 1 and 2 do not consider powders with a particle size of 2.0 μm or less.

[0006] [Patent Document 1] JP 2016-204236 A [Patent Document 2] JP 2015-86120 A Summary of the Invention

[0007] Therefore, an object of the present invention is to provide a silica powder having a particle size of 2.0 μm or less, which is resistant to aggregation, easy to handle, and easily disperses when mixed with a resin, as well as a resin composition and a semiconductor encapsulant containing the silica powder.

[0008] As a result of extensive investigation, the present inventors have found that the maximum particle diameter (D max The present inventors have found that all of the above problems can be solved by using a silica powder having a particle size of 5.0 μm or less, and have thus completed the present invention. That is, the present invention has the following aspects. [1] The volume-based cumulative diameter (D50) is 2.0 μm or less, and the maximum particle diameter (D max) is 5.0 μm or less. (Measurement method) To 100 parts by mass of bisphenol F type liquid epoxy resin, 67 parts by mass of silica powder is added, and the mixture is mixed using a rotating and revolving mixer at a temperature of 30°C and a rotation speed of 2,000 rpm for 3 minutes of rotation and 1 minute of revolution to prepare a resin composition. The resin composition is evaluated for the degree of dispersion of the silica powder in the epoxy resin by a distribution diagram method using a grind gauge with a width of 90 mm, a length of 240 mm, and a maximum depth of 100 μm according to JIS K 5600-2-5, and the maximum particle diameter (D max The same evaluation is carried out five times and the average value is used. [2] The silica powder according to [1], having a volume-based cumulative diameter (D90) of 2.5 μm or less. [3] The silica powder according to [1] or [2], having a volume-based cumulative diameter (D100) of 4.7 μm or less. [4] Specific surface area (BET) is 2 to 15 m 2 / g. The silica powder according to any one of [1] to [3]. [5] The silica powder according to any one of [1] to [4], wherein a volume-based frequency of the volume-based cumulative diameter (D90) relative to a difference between the volume-based cumulative diameter (D100) and the volume-based cumulative diameter (D90), calculated by the following formula (1), is 1.0 to 3.0: (Volume-based frequency of volume-based cumulative diameter (D90)) / (Volume-based cumulative diameter (D100) - Volume-based cumulative diameter (D90)) (1) [6] A resin composition comprising the silica powder according to any one of [1] to [5] and a resin. [7] The resin composition according to [6], wherein the resin comprises a thermosetting resin. [8] A semiconductor encapsulation material comprising the resin composition according to [6] or [7].

[0009] According to the present invention, it is possible to provide a silica powder having a particle size of 2.0 μm or less, which is resistant to aggregation, has good handleability, and is easily dispersed when mixed with a resin, as well as a resin composition and a semiconductor encapsulant each containing the silica powder. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in detail below, but the present invention is not limited to the following aspects. In this specification, the term "to" means "not less than or equal to." For example, "3 to 15" means 3 or more and not more than 15. In this specification, "powder" means "aggregation of particles."

[0011] [Silica powder] The silica powder according to the present invention has a volume-based cumulative diameter (D50) of 2.0 μm or less, and a maximum particle diameter (D max ) is 5.0 μm or less. (Measurement method) To 100 parts by mass of bisphenol F type liquid epoxy resin, 67 parts by mass of silica powder is added, and the mixture is mixed using a rotating and revolving mixer at a temperature of 30°C and a rotation speed of 2,000 rpm for 3 minutes of rotation and 1 minute of revolution to prepare a resin composition. The resin composition is evaluated for the degree of dispersion of the silica powder in the epoxy resin by a distribution diagram method using a grind gauge with a width of 90 mm, a length of 240 mm, and a maximum depth of 100 μm according to JIS K 5600-2-5, and the maximum particle diameter (D max The same evaluation is carried out five times and the average value is used.

[0012] The silica powder according to the present invention is less prone to aggregation, is easy to handle, and is easily dispersed when mixed with a resin.

[0013] The volume-based cumulative diameter (D50) of the silica powder according to the present invention (hereinafter, sometimes referred to as "D50") is 2.0 μm or less, preferably 1.5 μm or less, more preferably 0.3 to 1.2 μm, and particularly preferably 0.4 to 1.0 μm. Even if the silica powder according to the present invention has a D50 of 2.0 μm or less, it is difficult to aggregate and has good handling. In addition, since the particles are difficult to aggregate when mixed with a resin, the dispersibility is also good. In this specification, the volume-based cumulative diameter (D50) of the silica powder refers to a particle diameter corresponding to a cumulative value of 50% in the volume-based cumulative particle size distribution measured by a laser diffraction scattering method (refractive index: 1.50). The cumulative particle size distribution is represented by a distribution curve with the particle diameter (μm) on the horizontal axis and the cumulative value (%) on the vertical axis. The volume-based cumulative particle size distribution measured by the laser diffraction scattering method (refractive index: 1.50) is measured using a laser diffraction scattering type particle size distribution analyzer (manufactured by Beckman Coulter, Inc., product name "LS-13 320XR") and water (refractive index: 1.33) as the solvent, after dispersion treatment using an ultrasonic generator (manufactured by Sonic Materials Inc., product name "VC-505") for 2 minutes as pretreatment.

[0014] The maximum particle diameter (D) of the silica powder according to the present invention measured by a grind gauge using the above method max ) is less than 5.0 μm. The groove of the grind gauge is inclined and gradually becomes shallower. Therefore, if there is a particle whose diameter is larger than the depth of the groove, a linear trace will remain on the formed film. Therefore, by checking the trace on the formed film against the scale on the grind gauge, the presence or absence of aggregates and their particle diameter can be confirmed. In the measurement method of the grind gauge according to the present invention, max The term "maximum particle diameter (D)" refers to the value of the linear trace left at the position of the largest particle diameter among the linear traces left on the formed film of the grind gauge. In the present invention, the above evaluation is performed five times, and the average value is taken as the "maximum particle diameter (D max )".

[0015] As described above, the grind gauge measurement is performed on a resin composition in which silica powder is dispersed in a bisphenol F type liquid epoxy resin. This method makes it possible to evaluate the dispersibility and degree of aggregation of the silica powder when dispersed in a resin. The silica powder according to the present invention has a maximum particle diameter (D max ) is 5.0 μm or less, which means that aggregation of the silica powder in the resin is suppressed. In other words, the silica powder according to the present invention is easily dispersed when mixed with the resin and is not easily aggregated. The bisphenol F type liquid epoxy resin used in the grind gauge measurement is preferably one having a viscosity of 3,000 to 4,500 mPa·s (25° C.) and an epoxy equivalent of 160 to 175 g / eq. The maximum particle diameter (D max ) is preferably 4.5 μm or less, particularly preferably 4.0 μm or less.

[0016] The volume-based cumulative diameter (D90) (hereinafter sometimes referred to as "D90") of the silica powder according to the present invention is preferably 2.5 μm or less, more preferably 2.2 μm or less, and even more preferably 2.0 μm or less. D90 refers to the particle diameter at which the cumulative value corresponds to 90% in the volume-based cumulative particle size distribution measured in the same manner as the above-mentioned D50. In other words, D90 of 2.5 μm or less means that the silica powder contains fewer coarse particles due to aggregation.

[0017] The volume-based cumulative diameter (D100) of the silica powder according to the present invention (hereinafter, sometimes referred to as "D100") is preferably 4.7 μm or less, more preferably 4.2 μm or less, and even more preferably 4.0 μm or less. D100 refers to the particle diameter at which the cumulative value corresponds to 100% in the volume-based cumulative particle size distribution measured in the same manner as the above-mentioned D50 and D90. "D100 is 4.7 μm or less" means that there are substantially no coarse particles over 4.7 μm in the silica powder. Note that "substantially no" means that the proportion of coarse particles over 4.7 μm in the silica powder is less than 0.1 mass%. Such silica powder is easier to handle, and when it is used as a resin composition for semiconductor encapsulation, it is easier to reduce the risk of coarse particles getting into the gaps in the wiring and causing short circuit defects.

[0018] In the silica powder according to the present invention, the volume-based frequency of the volume-based cumulative diameter (D90) relative to the difference between the volume-based cumulative diameter (D100) and the volume-based cumulative diameter (D90), calculated from the following formula (1), is preferably 1.0 to 3.0, more preferably 1.5 to 3.0, and even more preferably 2.0 to 3.0. (Volume-based frequency of volume-based cumulative diameter (D90)) / (Volume-based cumulative diameter (D100) - Volume-based cumulative diameter (D90)) (1) In formula (1), the "volume-based frequency of the volume-based cumulative diameter (D90)" (hereinafter, sometimes referred to as "volume-based frequency of D90") means the frequency of the particle diameter corresponding to 90% of the cumulative value in the volume-based cumulative particle size distribution measured by the above-mentioned laser diffraction scattering method (refractive index: 1.50). If the volume-based frequency of D90 relative to the difference between D100 and D90 of the silica powder is within the above range, aggregation is less likely to occur and there are fewer coarse particles. Such silica powder is more likely to be easy to handle, and when it is made into a resin composition for semiconductor encapsulation, it is more likely to reduce the risk of coarse particles getting into the gaps in the wiring and causing short-circuit defects. In addition, the difference between D100 and D90 (D100-D90) is preferably 2.3 μm or less, more preferably 2.0 μm or less. If the difference between D100 and D90 is within the above range, the silica powder has a narrower particle size distribution. Such silica powder has fewer coarse particles and tends to have better dispersibility in resin.

[0019] The ratio of D50 to D90 (D90 / D50) of the silica powder according to the present invention is preferably 2.2 or less, more preferably 2.0 or less, and even more preferably 1.4 to 2.0. If D90 / D50 is 2.2 or less, the silica powder tends to have a narrower particle size distribution. Such a silica powder is preferable because it is less likely to aggregate and is easier to handle.

[0020] The ratio of D50 to D100 (D100 / D50) of the silica powder according to the present invention is preferably 5.0 or less, more preferably 4.0 or less, and even more preferably 3.0 to 4.0. If D100 / D50 is 5.0 or less, the silica powder tends to have a narrower particle size distribution. Such a silica powder is preferable because it is less likely to aggregate and is easier to handle.

[0021] In the silica powder according to the present invention, the specific surface area measured by the BET method is 2 to 15 m 2 / g, and 3 to 12m 2 / g is more preferable, and 3 to 8m 2 / g is even more preferable. The silica powder according to the present invention can have a relatively small specific surface area while having a D50 of 2.0 μm or less. The silica powder according to the present invention has a relatively narrow particle size distribution, with a small proportion of finer particles. In addition, since the aggregation of particles is suppressed, it is easy to achieve a specific surface area in the above range. In this specification, the measurement of the specific surface area by the BET method was performed using a "Macsorb HM model-1208" (manufactured by Mountec Co., Ltd.).

[0022] The silica powder according to the present invention is preferably an amorphous silica powder produced by melting a crystalline silica powder at high temperature, from the viewpoints of bringing the thermal expansion coefficients of the semiconductor chip and the liquid encapsulant closer together, solder heat resistance, moisture resistance, and low mold wear.

[0023] The silica powder according to the present invention is preferably a spherical silica powder, and more preferably a spherical amorphous silica powder. The degree of "sphericity" is preferably an average sphericity of 0.85 or more. The average sphericity can be calculated by importing particle images taken with a stereomicroscope (e.g., product name "Model SMZ-10" manufactured by Nikon Corporation), a scanning electron microscope, a transmission electron microscope, etc., into an image analyzer (e.g., manufactured by Nippon Avionics Co., Ltd.) and measuring as follows. That is, the projected area (A) and perimeter (PM) of the particle are measured from the photograph. If the area of ​​a perfect circle relative to the perimeter (PM) is (B), the circularity of the particle can be expressed as A / B. Therefore, assuming a perfect circle having the same perimeter as the perimeter (PM) of the sample particle, PM=2πr, B=πr 2 Therefore, B = π × (PM / 2π) 2 The sphericity of each particle is given by: Sphericity = A / B = A × 4π / (PM) 2 The sphericity of any 200 particles thus obtained is calculated, and the average value is taken as the average sphericity.

[0024] The silica powder may be treated with a surface modifier. By being treated with a surface modifier, the particles are less likely to aggregate with each other, and the dispersibility in the resin is likely to be improved. When the silica powder is treated with a surface modifier, the entire surface of the particles may be modified, or only a part of the surface may be modified.

[0025] The surface modifier is not particularly limited as long as it has the effect of the present invention, and any surface modifier that has been used for fillers such as silica powder can be used as appropriate. For example, silane compounds, silazane compounds, aluminate coupling agents, titanate coupling agents, etc. can be used. These may be used alone or in combination of two or more.

[0026] [Method of manufacturing silica powder] Next, one embodiment of the method for producing a silica powder according to the present invention will be described. The silica powder according to the present embodiment can be produced by classifying a raw material powder prepared by a conventional method. In this specification, the term "raw material powder" refers to a silica powder containing coarse particles before classification. The powder for preparing the raw material powder is referred to as a "crude raw material powder". As a method for producing the raw material powder, a conventionally known method can be used, and examples of such methods include a method in which a raw material powder is obtained by directly supplying a raw material powder into a high-temperature flame formed in a furnace, and a method in which a slurry containing the raw material powder is sprayed into the flame to remove the solvent, thereby obtaining the raw material powder.

[0027] Methods for classifying raw material powders are generally broadly divided into dry methods and wet methods. Examples of the dry method include sieve classification, air flow classification, etc. Examples of the wet method include filter classification, in which raw material powder is dispersed in a solvent and then passed through a filter or the like to remove coarse particles, and fluid classification, in which the raw material is made into a fluid and the difference in sedimentation velocity is used to remove coarse particles. In the production method according to the present embodiment, from the viewpoint of preventing a decrease in yield and preventing a decrease in dispersibility in the resin due to changes in particle size distribution or specific surface area, it is preferable that the production method includes air classification of the raw material powder to remove coarse particles.

[0028] Air classification is a method in which raw material powder is dispersed in an air current and coarse particles are removed by utilizing the gravity, inertial force, centrifugal force, etc. of the particles. Examples of the method using inertial force include an impactor type in which a guide vane or the like is provided inside the classifier to create a swirling air current, and the raw powder, which has been given momentum by the air current, is curved to remove coarse particles, a semi-free vortex centrifugal type in which centrifugal force is applied to the raw powder to classify it, and a Coanda type that uses the Coanda effect, etc. Examples of classifiers that use inertial force include a cascade impactor, a viable impactor, an aero fine classifier, an eddy classifier, an elbow jet, a hyperplex, and a Coanda block. An example of a method using centrifugal force is a method of removing coarse particles using a vortex airflow. Devices include free vortex type and forced vortex type. Free vortex type devices include cyclones without guide vanes, multi-stage cyclones, turboplexes that use secondary air to promote the elimination of agglomeration, dispersion separators with guide vanes to improve classification accuracy, microspins, microcuts, etc. Forced vortex types are devices that apply centrifugal force to particles with a rotating body inside the device and further improve classification accuracy by creating a separate airflow inside the device, and examples of such devices include turbo classifiers and Donaserec.

[0029] In the manufacturing method according to the present embodiment, from the viewpoints of production efficiency and classification accuracy, air classification using inertial force is preferable, and it is more preferable to include classifying the raw material powder by air classification using the Coanda effect. Also, from the viewpoint of classification accuracy, the air temperature is preferably less than 150°C, more preferably 40 to 130°C, and even more preferably 60 to 120°C.

[0030] The method for producing a silica powder according to this embodiment may include, for example, the following steps. (i) optionally, crushing and classifying the ore to obtain a crude powder; (ii) feeding the raw material powder into a high-temperature flame in a reaction vessel to produce raw material powder (molten powder); (iii) The raw powder is treated with an airflow classification using the Coanda effect at an airflow temperature of less than 150°C, and the maximum particle diameter (D max) is 5.0 μm or less to obtain a silica powder.

[0031] <Process (i)> The raw material used in step (i) is preferably one with high purity (for example, a purity of 95% or more). Examples of the raw material include metallic silicon, silica stone, etc. These may be used alone or in combination of two or more. Of these, it is more preferable that the raw material contains metallic silicon. The raw material is pulverized with a pulverizer such as a vibration mill or a ball mill to prepare a crude raw material powder having a desired particle size. The D50 of the crude raw material powder is preferably 5 to 40 μm, more preferably 5 to 20 μm, from the viewpoints of handling, oxidation, and spheroidization.

[0032] <Process (ii)> In step (ii), the raw powder obtained in step (i) is injected into a high-temperature flame formed by a combustible gas and a combustion supporting gas using a burner, melted and spheroidized at a temperature equal to or higher than the melting point or boiling point of the raw powder (for example, a temperature of 1600°C or higher in the case of silica (silica)), and classified and repaired while cooling to obtain a spheroidized raw powder (molten powder). In the case of metallic silicon, a metal powder slurry is supplied into a high-temperature flame consisting of a combustible gas and a combustion supporting gas in a production furnace at a temperature of 2400°C or higher, and the metal powder is vaporized and oxidized in the flame to obtain a raw powder. In step (ii), the D50 of the raw powder is preferably 0.2 to 2.0 μm, more preferably 0.2 to 1.5 μm. The combustible gases include hydrocarbon gases such as acetylene, ethylene, propane, butane, and methane; gaseous fuels such as LPG, LNG, and hydrogen; and liquid fuels such as kerosene and heavy oil. The supporting gases include oxygen, oxygen-rich cooling gas, and air.

[0033] In step (ii), the D50 of the raw material powder may be adjusted by adjusting the powder supply amount, the powder temperature, the temperatures of the combustible gas and the combustion supporting gas, and the like.

[0034] <Step (iii)> In step (iii), the raw powder obtained in step (ii) is treated by airflow classification using the Coanda effect at an airflow temperature of less than 150°C to obtain a powder having a D50 of 2.0 μm or less and a maximum particle diameter (D max ) is 5.0 μm or less to obtain a silica powder. As described above, the airflow temperature is more preferably 40 to 130°C, and even more preferably 60 to 120°C. The gas species used in the airflow may be any of air, oxygen, nitrogen, helium, argon, carbon dioxide, and the like. In order to make the volume-based cumulative diameter (D50) of the silica powder 2.0 μm or less, from the viewpoint of being less likely to aggregate, adjustment may be made by introducing nitrogen. The flow velocity of the airflow is preferably less than 80 m / s at the Coanda block inlet, more preferably 30 to 75 m / s, and even more preferably 35 to 50 m / s. By combining these conditions, wear caused by friction with the device is suppressed, and the dispersibility of particles in the airflow is further increased, making it easier to improve the Coanda effect.

[0035] [Resin composition] The resin composition according to the present invention contains the above-mentioned silica powder and a resin. The content of the silica powder in the resin composition is not particularly limited and can be appropriately adjusted depending on the purpose. From the viewpoint of heat resistance, thermal expansion coefficient, etc., the ratio of the silica powder in the resin composition is preferably 40 to 90 mass %, more preferably 70 to 90 mass %, based on the total mass of the resin composition. The silica powder according to the present invention has a D50 of 2.0 μm or less and a maximum particle diameter (D max Since the particle size is 5.0 μm or less, the dispersibility in the resin is good. Such a resin composition can be suitably used as a semiconductor encapsulant or a substrate for a semiconductor package.

[0036] (resin) The resin is preferably a thermosetting resin. The thermosetting resin is not particularly limited as long as it is one that is normally used in the field of semiconductor encapsulation materials. For example, epoxy resin; silicone resin; phenol resin; melamine resin; urea resin; unsaturated polyester resin; fluororesin; polyimide resin, polyamideimide resin, polyetherimide resin, and other polyimide-based resins; polyester resin, such as polybutylene terephthalate resin and polyethylene terephthalate resin; polyphenylene sulfide resin; wholly aromatic polyester resin; polysulfone resin; liquid crystal polymer resin; polyethersulfone resin; polycarbonate resin; maleimide modified resin; ABS resin, AAS resin (acrylonitrile-acrylic rubber-styrene resin), AES resin (acrylonitrile-ethylene-propylene-diene rubber-styrene resin), and the like; can be mentioned. These may be used alone or in combination of two or more. Of these, it is more preferable to include an epoxy resin.

[0037] The epoxy resin is not particularly limited, and examples thereof include phenol novolac type epoxy resins, orthocresol novolac type epoxy resins, epoxidized novolac resins of phenols and aldehydes, glycidyl ether type epoxy resins such as bisphenol A, bisphenol F and bisphenol S, glycidyl ester acid epoxy resins (bisphenol type epoxy resins) obtained by reacting polybasic acids such as phthalic acid and dimer acid with epochlorohydrin, linear aliphatic epoxy resins, alicyclic epoxy resins, heterocyclic epoxy resins, alkyl-modified polyfunctional epoxy resins, β-naphthol novolac type epoxy resins, 1,6-dihydroxynaphthalene type epoxy resins, 2,7-dihydroxynaphthalene type epoxy resins, bishydroxybiphenyl type epoxy resins, and epoxy resins into which halogens such as bromine have been introduced to impart flame retardancy. These may be used alone or in combination of two or more. Among these, it is more preferable to contain at least one epoxy resin selected from bisphenol type epoxy resins such as bisphenol A type epoxy resins and bisphenol F type epoxy resins, and alicyclic epoxy resins.

[0038] (hardening agent) When the resin contains an epoxy resin, the resin composition preferably further contains a curing agent. Examples of the curing agent include a novolac type resin obtained by reacting one or more mixtures selected from the group consisting of phenol, cresol, xylenol, resorcinol, chlorophenol, t-butylphenol, nonylphenol, isopropylphenol, octylphenol, etc. with formaldehyde, paraformaldehyde, or paraxylene under an oxidation catalyst, a polyparahydroxystyrene resin, a bisphenol compound such as bisphenol A or bisphenol S, a trifunctional phenol such as pyrogallol or phloroglucinol, an acid anhydride such as maleic anhydride, phthalic anhydride, or pyromellitic anhydride, and an aromatic amine such as metaphenylenediamine, diaminodiphenylmethane, or diaminodiphenylsulfone.

[0039] The content of the curing agent is preferably such that the active hydrogen equivalent (or acid anhydride equivalent) of the curing agent is 0.01 to 1.25 per 1 epoxy equivalent of the epoxy resin.

[0040] (Other additives) The resin composition may contain a curing accelerator, a release agent, a coupling agent, a colorant, etc., within the range not impairing the effects of the present invention. The curing accelerator is not particularly limited, and examples thereof include 1,8-diazabicyclo(5,4,0)undecene-7, triphenylphosphine, benzyldimethylamine, and 2-methylimidazole. Examples of the release agent include natural waxes, synthetic waxes, metal salts of straight-chain fatty acids, acid amides, esters, and paraffin. The coupling agent may be a silane coupling agent. Examples of the silane coupling agent include epoxy silanes such as γ-glycidoxypropyltrimethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; amino silanes such as aminopropyltriethoxysilane, ureidopropyltriethoxysilane and N-phenylaminopropyltrimethoxysilane; hydrophobic silane compounds such as phenyltrimethoxysilane, methyltrimethoxysilane and octadecyltrimethoxysilane, and mercaptosilane.

[0041] One embodiment of the resin composition according to the present invention contains the silica powder according to the present invention and a bisphenol F type epoxy resin, and has a maximum particle diameter (D max The resin composition has a maximum particle diameter (D max ) may be 4.0 μm. (Measurement method) To 100 parts by mass of bisphenol F type liquid epoxy resin, 67 parts by mass of silica powder is added, and the mixture is mixed using a rotating and revolving mixer at a temperature of 30°C and a rotation speed of 2,000 rpm for 3 minutes of rotation and 1 minute of revolution to prepare a resin composition. The resin composition is evaluated for the degree of dispersion of the silica powder in the epoxy resin by a distribution diagram method using a grind gauge with a width of 90 mm, a length of 240 mm, and a maximum depth of 100 μm according to JIS K 5600-2-5, and the maximum particle diameter (D max The same evaluation is carried out five times and the average value is used.

[0042] <Method of producing resin composition> The method for producing the resin composition is not particularly limited, and the resin composition can be produced by stirring, dissolving, mixing, and dispersing a predetermined amount of each material. The apparatus for mixing, stirring, dispersing, etc. of the mixture is not particularly limited, but a mortar and pestle machine equipped with a stirring and heating device, a three-roll mill, a ball mill, a planetary mixer, etc. can be used. These apparatuses may also be used in appropriate combination.

[0043] [Semiconductor encapsulation materials] The semiconductor encapsulant according to the present invention is produced using the resin composition according to the present invention. Specifically, the resin composition is first kneaded while being heated with a roll or an extruder, and the kneaded product is stretched into a sheet and cooled. Thereafter, the kneaded product is pulverized, or the kneaded product is extruded into a linear shape, cooled, and then cut, to obtain a semiconductor encapsulant as a pulverized product of the resin composition. The pulverized product may be formed into a shape such as a tablet or pellet.

[0044] As a method for encapsulating a semiconductor using the semiconductor encapsulant according to the present invention, a conventionally known method such as a transfer molding method or a compression molding method can be used. An example of the transfer molding method is a method in which a tablet-shaped semiconductor encapsulant is loaded into a pot attached to a mold of a transfer molding machine, heated to melt it, and then pressed with a plunger and further heated to harden the encapsulant. An example of the compression molding method is a method in which a pellet- or tablet-shaped sealing material is placed directly in a mold and melted, and then the bonded chip or wafer is immersed in molten resin and heated to harden. EXAMPLES

[0045] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following description.

[0046] [Examples 1 to 4 and Comparative Examples 1 to 7] (Production of raw material powder: steps (i) to (ii)) A triple-wound tube burner, consisting of a flammable gas supply pipe, a combustion supporting gas supply pipe, and a metal silicon powder slurry supply pipe, arranged in this order from the outermost side, was installed at the top of the manufacturing furnace, and the raw material powder was manufactured using an apparatus in which the lower part of the manufacturing furnace was connected to a classification and collection system such as a cyclone (the generated particles were sucked in by a blower and collected by a bag filter). Three more peripheral burners were installed on the outer periphery of the burner to form a peripheral flame. LPG was supplied from the flammable gas supply pipe at a rate of 7 Nm3 / hr, oxygen 12Nm from the combustion support gas supply pipe 3 / hr to form a high-temperature flame in the manufacturing furnace. Metallic silicon slurry prepared by dispersing metallic silicon powder (average particle size (D50): 10 μm) in methyl alcohol was fed into the flame from a metallic silicon powder slurry feed pipe using a slurry pump, and the resulting raw material powder (spherical silica powder) was collected by a cyclone or bag filter at a powder temperature of 110°C to 200°C. The particle size and specific surface area of ​​the raw material powder were adjusted by controlling the metallic silicon concentration in the furnace through adjustment of the slurry concentration. Through these operations, raw material powders with D50 of 0.5 μm, 0.7 μm, 1.0 μm, 1.5 μm, 1.9 μm, and 2.6 μm were obtained.

[0047] (Classification of raw material powder: step (iii)) Each of the raw material powders obtained above was classified under the conditions shown in Table 1 to obtain silica powders of each example. The classification operation involved feeding the raw material powder to an air classifier having a Coanda block structure using a blower (manufactured by Matsubo Corporation, product name "Elbow Jet Classifier") for air classification, and then collecting the powder using a bag filter. Nitrogen gas or air (dew point temperature: -5°C) was used as the gas for the airflow. The gas temperature of the airflow and the flow rate of the Coanda section were as shown in Table 1.

[0048] (Measuring method of grind gauge) The maximum particle size (D max ) was measured under the following conditions. To 100 parts by mass of bisphenol F type liquid epoxy resin (manufactured by Mitsubishi Chemical Corporation, product name "807", viscosity: 3,000-4,500 mPa·s, epoxy equivalent: 160-175 g / eq.), 67 parts by mass of silica powder was added, and the mixture was mixed at a temperature of 30°C and a rotation speed of 2,000 rpm with rotation for 3 minutes and revolution for 1 minute using a planetary centrifugal mixer (manufactured by Thinky Corporation, product name "ARE-310") to prepare a resin composition. The obtained resin composition was evaluated for the degree of dispersion of the silica powder in the epoxy resin by a distribution diagram method using a grind gauge with a width of 90 mm, a length of 240 mm, and a maximum depth of 100 μm according to JIS K 5600-2-5, and the maximum particle diameter (D max The same evaluation was carried out five times, and the average value was used. The results are shown in Table 1.

[0049] (Measurement of volume-based cumulative diameter (D50, D90, and D100)) The silica powder obtained in each example was dispersed in water (refractive index: 1.33) as a solvent for 2 minutes using an ultrasonic generator (SONICS MATERIALS INC., product name "VC-505") using a particle size distribution analyzer (Beckman Coulter, Inc., product name "LS-13 320XR"), and then the volume-based frequency particle size distribution was measured using the laser diffraction light scattering method. The volume-based frequency of D90 and the values ​​of D100 and D90 were calculated by applying them to the above formula (1). These results are shown in Table 1.

[0050] (Measurement of specific surface area (BET)) For the silica powder obtained in each example, 1.0 g of the silica powder was weighed out and placed in a measurement cell. After pretreatment, the BET specific surface area was measured using nitrogen gas. The measuring device used was a "Macsorb HM model-1208" manufactured by MACSORB. The specific surface area was measured under the following conditions. The results are shown in Table 1. Degassing temperature: 300℃ Degassing time: 18 minutes Cooling time: 4 minutes.

[0051] [Table 1]

[0052] As shown in Table 1, the silica powders of Examples 1 to 4 had a maximum particle diameter (D max ) was 5.0 μm or less. That is, a silica powder was obtained that was less likely to aggregate and was easily dispersed even when mixed with a resin. It was also found that such a silica powder can be easily obtained by classifying raw material particles at a lower gas temperature and low flow rate using nitrogen gas. In addition, the results of Comparative Examples 1 to 7 showed that the silica powder was easily aggregated in the resin when classification was not performed and when classification was performed in air. [Industrial Applicability]

[0053] As described above, the silica powder according to the present invention has the characteristics that it is difficult to aggregate, easy to handle, and easy to disperse when mixed with a resin, while having a D50 of 2.0 μm or less. A resin composition containing such silica powder can be suitably used as a semiconductor encapsulant.

Claims

1. The volume-based cumulative diameter (D50) is 2.0 μm or less, and the maximum particle diameter (D max ) is 5.0 μm or less and the specific surface area (BET) is 2 to 15 m 2 / g. (Measurement method) To 100 parts by mass of bisphenol F type liquid epoxy resin, 67 parts by mass of silica powder is added, and the mixture is mixed using a planetary centrifugal mixer at a temperature of 30° C. and a rotation speed of 2,000 rpm for 3 minutes of rotation and 1 minute of revolution to prepare a resin composition. The resin composition was measured using a grind gauge having a width of 90 mm, a length of 240 mm, and a maximum depth of 100 μm according to JIS K 5600-2-5, and the degree of dispersion of the silica powder in the epoxy resin was evaluated by a distribution map method. max The same evaluation is carried out five times, and the average value is used.

2. 2. The silica powder according to claim 1, having a volume-based cumulative diameter (D90) of 2.5 μm or less.

3. The silica powder according to claim 1 or 2, having a volume-based cumulative diameter (D100) of 4.7 μm or less.

4. 3. The silica powder according to claim 1, wherein the volume-based frequency of the volume-based cumulative diameter (D90) relative to the difference between the volume-based cumulative diameter (D100) and the volume-based cumulative diameter (D90), calculated from the following formula (1), is 1.0 to 3.

0. (Volume-based frequency of volume-based cumulative diameter (D90)) / (volume-based cumulative diameter (D100)-volume-based cumulative diameter (D90)) (1)

5. A resin composition comprising the silica powder according to claim 1 or 2 and a resin.

6. The resin composition of claim 5 , wherein the resin comprises a thermosetting resin.

7. A semiconductor encapsulant comprising the resin composition according to claim 5 .

Citation Information

Patent Citations

  • Epoxy resin silica sol, epoxy resin organic-inorganic nano hybrid material and preparation method thereof

    CN103044857A

  • High stably dispersed nano-silica filled epoxy resin system, cured product and preparation method thereof

    CN104497494A

  • Spherical metal oxide powder, its manufacturing method and use thereof

    JP2007070159A

  • Dry silica particle package

    JP2009298461A

  • Stabilized hdk suspension for reactive resin strengthening

    JP2009503166A